IMMUNOHISTOCHEMICAL EXPRESSION OF BRAFV600E IN MELANOMA CASES: BRAFV600E Expression in Melanoma Cases - Ch, Muhammad Umer; Akhtar, Farhan; Jamal, Nighat; Ahmad, Rabia; Bukhsh, Sumaira; Mansur, Hamza (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the diagnostic value of Immunohistochemistry (IHC) for finding BRAFV600E mutation in melanoma patients.Study Design: Cross-sectional study.Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, Jan 2018 to Apr 2019.Methodology: Hundred histologically confirmed cases of melanoma aged between 18-80 years were included over a period of one year. To create the tissue microarray and to conduct immunohistochemistry with VE1 antibody melanoma lesion samples were selected.Results: Ninety-four cases out of 100, were melanoma positive for BRAFV600E detected on immunohistochemistry (IHC) using a monoclonal antibody. The skin was the primary site in seventy-nine (79%) patients, unknown (metastatic) in nineteen and uveal was only in two cases. The diagnostic significance of immunohistochemistry (IHC) for detecting the BRAFV600E mutation in melanoma patients was independent of age, site and stage at diagnosis (p-value